The Positions Mainstream Left Parties Adopt on Immigration: A Crosscutting Cleavage? - Carvalho, João; Ruedin, Didier (My University, 2018)
Immigration is often perceived as a political topic that overlaps traditional ideological cleavages. Much research has focused on the positions of the extreme right, and little research has examined mainstream parties and their public stances on immigration. This shortcoming hampers broader understanding of political competition on this issue. Drawing on a political claims analysis of seven countries between 1995 and 2009, we present the salience, position and overall coherence of claims made by mainstream parties on immigration control and immigrant integration. Mainstream left parties adopt a more positive/expansive position on immigration and exhibit higher levels of coherence than centrist and right-wing parties. We also show that the impact of extreme-right parties on the political claims of mainstream left parties seems to be limited. Our conclusions highlight that immigration does not necessarily constitute a cross-cutting cleavage across mainstream left parties: Their ideological preferences remain aligned with their positive/liberal discourse on immigration control and immigrant integration.